The Influence Of Political Connections and Capital Intensity On Tax Aggressiveness - Fransiska, Saskia Dwi; Anggara, Yulius Rizki Deka; Anggraeni, Sesilia Eva; Sinaga, Imelda; Purwati, Agnes Susana Merry (GOVERNORS, 2024)
Companies conduct tax aggressiveness (tax avoidance) to minimize the company's tax burden by utilizing loopholes in tax regulations. The purpose of this study is to analyze the effect of political connections and capital intensity. The population of this study are manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The number of samples used in this study were 30 samples based on purposive sampling method. The data analysis method in this study is quantitative analysis using multiple linear regression analysis. The results of this study indicate that political connections and capital intensity have no effect on tax aggressiveness.  The results of this study indicate that simultaneously Political Connection and Capital Intensity have no effect on Tax Aggressiveness. Partially, Political Connection has no significant positive effect on Tax Aggressiveness, while Capital Intensity has no significant negative effect on Tax Aggressiveness. The relationship between tax planning and agency theory is that in this case the government (tax authorities) as the principal and management as the agent each have different interests in terms of paying taxes.